(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the importance of social norms and human values in artificial intelligence systems. It emphasizes the necessity of considering justice, equality, moral responsibility, and human values in the development and implementation of artificial intelligence. Based on social and philosophical approaches, the article substantiates the importance of aligning artificial intelligence technologies with human interests. Artificial intelligence, grounded in ethical principles, equality, justice, and human values, contributes to social stability and the development of human potential.